Citrus Leprosis Virus C Encodes Three Proteins With Gene Silencing Suppression Activity - Leastro, Mikhail Oliveira; Castro, Deibis Yorlenis Ortega; Freitas-Astúa, Juliana; Kitajima, Elliot Watanabe; Pallás, Vicente; Sánchez-Navarro, Jesús Ángel (Frontiers in Microbiology, 2020)
Citrus leprosis virus C (CiLV-C) belongs to the genus Cilevirus, family Kitaviridae, and is considered the most devastating virus infecting citrus in South America, being the main viral pathogen responsible for citrus leprosis (CL), a severe disease that affects citrus orchards in Latin America. Here, proteins encoded by CiLV-C genomic RNA 1 and 2 were screened for potential RNA silencing suppressor (RSS) activity by five methods. Using the GFP-based reporter agroinfiltration assay, we have not found potential local suppressor activity for the five CiLV-C encoded proteins. However, when RSS activity was evaluated using the alfalfa mosaic virus (AMV) system, we found that the p29, p15 and p61 CiLV-C proteins triggered necrosis response and increased the AMV RNA 3 accumulation, suggesting a suppressive functionality. From analysis of small interfering RNAs (siRNAs) accumulation, we observed that the ectopic expression of the p29, p15 and p61 reduced significantly the accumulation of GFP derived siRNAs. The use of the RSS defective turnip crinkle virus (TCV) system revealed that only the trans-expression of the p15 protein restored the cell-to-cell viral movement, indicating that p15 has the ability to complement the RSS defective activity in the TCV mutant. Finally, using the potato virus X (PVX) system, the p29, p15 and p61 expression increased the PVX RNA accumulation; in addition, the p29 and p15 enhanced the pathogenicity of PVX resulting in the death of tobacco plants. Furthermore, PVX-p61 infection resulted in a hypersensitive response (HR), suggesting that the p61 could also activate a plant defense response mechanism. This is the first report describing the RSS activity for CiLV-C proteins and, moreover, for a member of the family Kitaviridae.